2015
DOI: 10.1097/ico.0000000000000360
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Confocal Microscopy of Pine Processionary Caterpillar Hair–Induced Keratitis

Abstract: To the best of our knowledge, this is the first case of corneal in vivo confocal imaging of a caterpillar hair with confirmation by ex vivo microscopy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
16
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 9 publications
0
16
0
Order By: Relevance
“…Setae are considered a rich source of allergens (Lamy et al, 1986;Rodriguez-Mahillo et al, 2012). These enter the skin at the site of setae penetration, either through direct contact with live or dead larvae or as a result of wind dispersal (aero-mediated contamination), which can occur over considerable distances and lead to an immune response in infected people and animals (Artola-Bordás, Arnedo-Peña, Romeu-García, & Bellido-Blasco, 2008;Battisti, Larsson, & Roques, 2017;Bonamonte, Foti, Vestita, & Angelini, 2013;Julienne et al, 2015;Kaszak, Planellas, & Dworecka-Kaszak, 2015;Moneo et al, 2015;Pouzot-Nevoret et al, 2017;Rodriguez-Mahillo et al, 2012;Vega et al, 2011Vega et al, , 2003.…”
mentioning
confidence: 99%
“…Setae are considered a rich source of allergens (Lamy et al, 1986;Rodriguez-Mahillo et al, 2012). These enter the skin at the site of setae penetration, either through direct contact with live or dead larvae or as a result of wind dispersal (aero-mediated contamination), which can occur over considerable distances and lead to an immune response in infected people and animals (Artola-Bordás, Arnedo-Peña, Romeu-García, & Bellido-Blasco, 2008;Battisti, Larsson, & Roques, 2017;Bonamonte, Foti, Vestita, & Angelini, 2013;Julienne et al, 2015;Kaszak, Planellas, & Dworecka-Kaszak, 2015;Moneo et al, 2015;Pouzot-Nevoret et al, 2017;Rodriguez-Mahillo et al, 2012;Vega et al, 2011Vega et al, , 2003.…”
mentioning
confidence: 99%
“…However, due to their small diameter, barbed morphology and penetration, hair removal is not possible in most cases. Indeed, Jullienne et al reported they could only remove 20 per cent of the hairs in their patient.…”
Section: Discussionmentioning
confidence: 95%
“…This caterpillar is considered one of the main forest pests and is present in extensive regions of central Asia, northern Africa and southern Europe. Reports on the toxicity of this insect can be found in medical and veterinary literature. Most cases are European or Indian, but toxicity by similar lepidopters (an order of insects that includes butterflies and moths) has also been reported in Australia…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations